Analisis Kelayakan Bisnis Toko Sola Pancing - Lubis, Putri Kemala Dewi; Tinambunan, Fitry Ulinda; Manurung, Eka Valentina; Siagian, Eny Juliana (CV. Rayyan Dwi Bharata, 2025)
A business feasibility study is an important step in determining the potential success of a business, including a shop. This article analyses various aspects that affect the operation and profitability of such businesses, including legal, marketing, and financial aspects. In the legal aspect, the importance of licensing and regulatory compliance are identified as determinants of consumer confidence. In terms of marketing, strategies such as market segmentation, promotion, and strategic location selection can increase the attractiveness of stores to customers. Financial analyses were conducted by assessing revenue, costs, profitability, as well as liquidity and solvency ratios to gauge profit potential. The results of the analysis show that this grocery store has a great opportunity to grow if managed properly. In conclusion, a comprehensive feasibility study is essential to ensure long-term success in business.